Smoothness Properties of Modified Bernstein-Kantorovich Operators. (2nd January 2016) - Özarslan, Mehmet Ali; Duman, Oktay
ABSTRACT: In this article, we consider modified Bernstein-Kantorovich operators and investigate their approximation properties. We show that the order of approximation to a function by these operators is at least as good as that of ones classically used. We obtain a simultaneous approximation result for our operators. Also, we prove two direct approximation results via the usual second-order modulus of smoothness and the second-order Ditzian-Totik modulus of smoothness, respectively. Finally, some graphical illustrations are provided.